Carnosol inhibits Hedgehog signaling pathway in both LNCaP and DU145 prostate cancer cell lines - Gao, H.; Song, Q.; Yang, J.; Yu, S.; Zhao, J.; Yu, G. (Cellular and Molecular Biology, 2017)
To investigate the effect of carnosol on the Hedgehog (HH) signaling pathway in human hormone-dependent prostate cancer cell line LNCaP and hormone-independent prostate cancer cell line DU145. The expression levels of glioma-associated oncogene homolog 1 (Gli1) and Sonic hedgehog (Shh) in human prostate cancer tissues were detected by immunohistochemistry. After treated with carnosol (0.25-16 Î¼mol/L), the cell survival of LNCaP and DU145 cells were detected by MTT assay. The expression levels of Gli1 and Shh mRNA and protein in the two cells were detected by qRT-PCR and western blot, respectively. The apoptosis was determined by the caspase-3 activity assay. Results showed that Shh and Gli1 were upregulated in cancer tissues. The inhibitory effect of carnosol on cell survival was enhanced with concentration, suggesting both LNCaP and DU145 cells were sensitive to carnosol. The inhibitory effects of carnosol on Gli1 and Shh mRNAs in the hormone-dependent LNCaP prostate cancer cell was stronger than that in the hormone-independent DU145 prostate cancer cells. Carnosol downregulated the expression of Gli1 in nucleus, and Shh in cells. Greater carnosol concentration resulted in lower levels of Gli1 and Shh. Carnosol increased caspase-3 activity in a dose-dependent manner, suggesting that carnosol promotes cell apoptosis. Thus, carnosol can inhibit the proliferation and induce the apoptosis of prostate cancer cells in vitro, and its mechanism might be associated with the inhibiting of HH signaling pathway. Although the inhibitory effect of carnosol on hormone-dependent LNCaP prostate cancer cells is stronger than hormone-independent DU145 prostate cancer cells, carnosol might be a potential drug for hormone-independent prostate cancer.